ETHNOSCIENCE STUDY OF YUR LOCAL WISDOM OF KANUM TRIBE IN MERAUKE - Ivylentine Palittin; Trinovianto George Reinhard Hallatu (Lembaga Pengembangan Pembelajaran Penelitian dan Pengabdian Masyarakat Universitas PGRI Mahadewa Indonesia, 2023)
Kanum tribe is one of indigenous tribes in Merauke which depend their live on nature. One of their local wisdoms is yur, which was done on plant at harvest time. The principle of yur is prohibits human to take that plant at the certain time. The aim of this research is to describe yur local wisdom with ethno-science study. This research conducted in Tomer village, habitat of Kanum tribe in Naukenjerai District, Merauke. Data collected direct observation to Tomer village, interview with some people of Kanum tribe, and also literature study. The result of this study show that yur local wisdom can analyze with biology, physic, and chemistry science. This local wisdom can protect every step of plant growing, namely pollination, fertilization, development of ovule into seed, ovary into fruit, and until it becomes a perfectly ripe fruit. Furthermore, yur can take care of imbibition, photosynthesis, and transpiration process. Finally, from all of that, yur can conserve the growing process of plant until harvest time.